Senneolittiske hellekister i Syd-Norge: En interimrapport - Einar, Østmo (In Situ Archaeologica, 2002)
”Late Neolithic stone cists in Southern Norway - a preliminary report”: In the late 19th and early 20th centuries, some six Late Neolithic stone cists or gallery graves were discovered and partly investigated in S Norway. The investigations were never properly published.In recent years, additional investigations have brought the number of known graves of this kind up to about twelve. Five of these have been dated to LN I and II; these are found widely dispersed in S Norway from Østfold to Lista. Another seven occur concentrated in eastern Østfold, these have been dated to LN II and ought to be considered together with those found in the adjacent Swedish districts.